The effect of differences pH medium fermentation on production and characterization of bacteria cellulose from oil palm frond juice - Arief Fazlul Rahman; Iffadhya Fathin Adiba; Fachri Ibrahim Nasution (Jurnal Agrotek Ummat, 2026)
Oil palm frond juice is a byproduct of the palm oil harvesting process, containing frond juice containing glucose, sucrose, and fructose. They are suitable for use as a fermentation raw material, thereby increasing the added value of the fronds. As a fermentation medium, frond juice does not inhibit microbial growth and poses no health or safety risks. The purpose of this study was to determine the effect of fermentation medium pH on bacterial cellulose from oil palm frond juice. Bacterial cellulose was produced using Acetobacter Xylinum. Oil palm frond juice was prepared at 100 ml/g with the addition of protein with different pH media fermented for 8 days at room temperature in statistical conditions. The results of the thickness and weight of the best cellulose bacteria of pH 5 medium were 0.78 cm and 393.015 g/L. FE-SEM micrograph analysis for bacterial cellulose showed typical peaks found in cellulose with typical fibril threads. pH 3 had the lowest crystallinity value and the best crystallinity was at pH 5 based on FWHM. 1106 and 1423 cm-1 wave number is the C-O-C or C-O bond areas which are one of the bonds of the main chain of bacterial cellulose and the best result tensile strength is the pH 5 treatment with a strength of 261.645 MPa